Retraction Note: Parents' Supernatural Beliefs on Causes of Birth Defects: A Review from Islamic Perspective - Çaksen, Hüseyin (Journal of Pediatric Genetics, 2024)
The above article published in Journal of Pediatric Genetics in Volume 12, Number 02 (DOI: 10.1055/s-0043-1761268), has been retracted as it is lacking scientific base.